Webster's Response to Alyssa Lyra Pitstick, Light in Darkness - Webster, John (Scottish journal of theology, 2009)
Though rarely addressed in a direct way, the theology of God's perfection is a central point at issue in contemporary Christian dogmatics. A good many debates of the moment turn on how the perfection of God's life is to be conceived: debates about the relation of the so-called immanent and economic Trinity; about the propriety of explicating the person and work of Christ through the metaphysics of divine and human natures; about the applicability of kenosis to account for the relation of the divine Word to the human career of Jesus; about the constitutive significance of temporality for the being of God; and much else besides. Recent disagreements amongst Barth scholars about the issue of the relation of the doctrine of divine election and the doctrine of the Trinity are in some measure animated by differing conceptions of the perfection of God, and one of the many ways of profiting from Dr Pitstick's book is to read it as, in part at least, an essay in defence of a certain construal of divine perfection. Indeed, one of my hopes for the book is that, once the noise of battle has subsided and the wounded have been dressed and taken to shelter, we may be able to engage peaceably and constructively with some of the material dogmatic issues to which it has drawn our attention. I do not propose to comment in detail on Dr Pitstick's evaluation of Balthasar; any judgements I might reach would be those of a mere amateur, one of those Protestants who in the 1970s discovered in Balthasar something which kept us reading Roman Catholic theology after Lonergan had wearied us and before we had been pointed to the treasures of ressourcement theology. Instead, I want to draw out from the book three doctrinal topics of capital importance: the ‘finished’ character of the redemptive work of Christ on the cross; the relation between theology and economy in the doctrine of the Trinity; and the doctrine of the hypostatic union – in all of which topics, of course, we are pressed to attend to the perfection of God and the acts of God.